Hot corrosion behavior of AlCoCrFeNiZr high entropy alloy (HEA) coating system exposed to Na2SO4-V2O5 salt - Odabas, Okan; Ozgurluk, Yasin; Karaoğlanlı, Abdullah Cahit; Özgürlük, Yasin; Karaoğlanlı, Abdullah Cahit (Elsevier, 2025)
This study investigated the hot corrosion behavior of AlCoCrFeNiZr high entropy alloy (HEA) top coatings with CoNiCrAlY bond coatings. CoNiCrAlY bond coatings were deposited on a Inconel 718 nickel-based superalloy substrate using an high-velocity oxy-fuel (HVOF) technique. HEA coatings were deposited on a CoNiCrAlY bond coats using an atmospheric plasma spraying (APS) process. The coatings were subjected to hot corrosion tests at 700 degrees C and 800 degrees C in a molten salt environment containing 45 % Na2SO4 and 55 % V2O5. The microstructural aspects and phase analyses were evaluated by energy dispersive spectroscopy (EDS) equipped scanning electron microscopy (SEM) and x-ray diffraction (XRD) methods. The results obtained from the hot corrosion tests and subsequent analyses showed that the AlCoCrFeNiZr HEA coating system maintained its structural integrity against hot corrosion damage despite approximately 30-35 % damage.
Keywords: High-Entropy Alloy (Hea); Alcocrfenizr; Conicraly; Hot Corrosion; Na2so4